Profile of Critical Thinking Ability of Class VIII State Middle School Students in Science Learning - Zalpita Agustia; Yennita Yennita; Fakhruddin Fakhruddin (Journal of Education and Learning Research, 2024)
Students' critical thinking abilities are very necessary to shape students' cognitive strengths. This research aims to determine the profile of students' critical thinking abilities in science learning. This type of research is exploratory descriptive research with a qualitative approach. The sample for this research consisted of 124 class VIII students at SMP Negeri 10 Tapung and data collection was carried out using the test method. The critical thinking ability test refers to indicators according to Ennis which consist of 8 indicators and the results are grouped into very high, high, medium, low and very low categories. The research results showed that 19% of students were in the very low category, 57% in the low category, 23% in the medium category, 1% in the high category, and there were no students in the high critical thinking ability category. Overall, students' critical thinking skills are in the low category with an average score of 31.50. Thus, for further research it is highly hoped that a method will be implemented to improve critical thinking skills.